Recommendations for Helping Cooperating Teachers Support Teacher Candidates with edTPA. (4th May 2022) - Parkes, Craig; Baxter, Deborah; Holden, Shelley
Abstract: The aim of this manuscript is to provide PHETE program coordinators/faculty with recommendations for improving CTs ability to better support TCs during the physical and health education edTPA process. The authors will provide specific examples of how they used their own empirical research findings to improve edTPA success within their respective undergraduate PHETE programs.